Performance Evaluation Testing of Automated Concentration Monitoring Device of Dust in Flue Gas Using Test Duct - Masashi Wada; Masashi Tsuji; William Averdieck (Current Overview on Science and Technology Research Vol. 7, 2022)
In this study, the issue in which the equivalence with gravimetric measurements cannot be universally measured was verified when the probe electrification type device, one of the main types of dust monitors, was evaluated using a test duct. Dust concentrations in industrial operations may now more easily be measured automatically. In order to further the technology in Japan, a number of JIS standards were created by 2020. In order to investigate the actual tests of performance evaluation in line with JIS standards, the validity and problems of the performance evaluation method employing test ducts were addressed in this study. The change in the dust charge broke the linear relationship between the dust metre readings and the gravimetric measurement, and a curvilinear relationship was observed in which the higher the dust concentration, the lower the dust readings. The test dust showed signs of a dust charge that might have resulted from frictional charging with the agitator plate and rectifying wire mesh. Dust concentration had a considerable impact on the dust charge, but not velocity, which was inversely proportional. It is concluded that it is necessary to measure the dust charge and compensate for it appropriately when conducting the equivalence test when using this test duct. In addition, it is desirable to take measures to fundamentally reduce the amount of dust charge generated.